Towards a Collective-Values Framework of Ubuntu: Implications for Workplace Commitment - Thembisile Molose; Geoff Goldman; Peta Thomas (Entrepreneurial Business and Economics Review, 2018)
Objective: This research offers an extension of current research on commitment across cultures. It incorporates the concept of Ubuntu as an integrating model that can be paired up with other perspectives for directing employee workplace commitment. Research Design & Methods: A literature review entailing concepts related to cross-cultures and their relationship to Ubuntu and commitment was considered. The review spanning 50 years covered online-databases of global and African research. Findings: We argue here that the conceptualisation of Ubuntu is important in adapting currently accepted cultural frameworks as operationalised by individualism, collectivism and power distance dimensions for regional management application. Ubuntu collective values (compassion, survival, group solidarity, respect and dignity), which relate affirmatively with a sense of workplace collectivism, was identified as a unique element of cultural management philosophy for directing personal interactions, workplace commitment and performance management improvements. Implications & Recommendations: Ubuntu should be facilitated by managers as a motivational force that facilitates workplace commitment ensuring organisational team performance. The implications of Ubuntu in the context of extending existing theories of individualism-collectivism and power distance cannot be overstated. Contribution & Value Added: A model based on relationships between Ubuntu collective values and EWC, applicable with contextual managerial frameworks.